Effect of Modified Atmosphere Composition on the Metabolism of Glucose by Brochothrix thermosphacta - Pin, Carmen (American Society for Microbiology, 2002)
The influence of atmosphere composition on the metabolism of Brochothrix thermosphacta was studied by analyzing the consumption of glucose and the production of ethanol, acetic and lactic acids, acetaldehyde, and diacetyl-acetoin under atmospheres containing different combinations of carbon dioxide and oxygen. When glucose was metabolized under oxygen-free atmospheres, lactic acid was one of the main end products, while under atmospheres rich in oxygen mainly acetoin-diacetyl was produced. The proportions of the total consumed glucose used for the production of acetoin (aerobic metabolism) and lactic acid (anaerobic metabolism) were used to decide whether aerobic or anaerobic metabolism predominated at a given atmosphere composition. The boundary conditions between dominantly anaerobic and aerobic metabolisms were determined by logistic regression. The metabolism of glucose by B. thermosphacta was influenced not only by the oxygen content of the atmosphere but also by the carbon dioxide content. At high CO(2) percentages, glucose metabolism remained anaerobic under greater oxygen contents.